Clinical profile, complications, morbidity and outcome of empyema thoracis in children in a tertiary care centre - Agarwal, Neha; Taneja, Sunil; Saxena, Rachit; Verma, Ashish (International Journal of Contemporary Pediatrics, 2018)
Background: Empyema thoracis, an accumulation of pus in pleural space, occurs in 5-10% of children with bacterial pneumonia. Often cases are referred to the tertiary care hospital late resulting in significant complications, morbidity and mortality. Our aim was to study the clinical profile, associated complications, morbidity and treatment outcome of empyema in children. Methods: A prospective observational study was conducted on 65 children aged 0-12 yrs diagnosed with empyema thoracis admitted in the hospital. After history taking and clinical examination, relevant investigations like chest X-ray, USG chest and pleural fluid analysis including culture and sensitivity were done. All patients were treated with chest tube drainage, antibiotics and intrapleural fibrinolytic therapy. Results: Maximum patients (61.5%) were seen in age group 1-5 yrs, 18.4% below 1 year, 2 were neonates. Pleural fluid culture was positive in 64.6 % of patients. Staphylococcus aureus (58.4%) was the most frequent organism isolated from pleural fluid. Pyopneumothorax (36.9%), broncho-pleural fistula (27.6%) and pneumothorax (18.4%) were common complications. Broncho-pleural fistula was present at admission in 14 patients, developed later in 4 patients and healed with conservative management in 12 patients. Majority of the patients (n=51, 78.4%) had complete resolution of empyema thoracis with re-expansion of lung on conservative management alone. The success rate of medical management in patients who received intrapleural fibrinolytic (streptokinase) within 14 days of symptom onset was 93.3% while it was 71.4% in patients who received intrapleural fibrinolytic after 14 days. 5 (7.6%) patients died, 5 required surgical intervention(decortication/VATS), 4 patients with broncho-pleural fistula not improving on conservative management were referred to higher centre and were lost to follow-up. Conclusions: Empyema in children causes significant morbidity which can be reduced by prompt and adequate treatment of bacterial pneumonia. Antibiotics, chest tube drainage along with intrapleural fibrinolytic therapy is a safe and effective method to facilitate drainage and resolution of empyema even in cases with delayed presentation in resource poor settings and can reduce the need for surgery.